Exploring elementary and middle school science teachers' metadiscourse moves: a Vygotskian analysis and interpretation. (2nd January 2021) - Soysal, Yilmaz
ABSTRACT: This study intended to explore elementary and middle school science teachers' metadiscourse moves (MDMs) in Vygotskian perspective. MDMs indicates teacher-led attempts to cognitively engage students in classroom's verbal occurrences. Participants of the study were 71 fifth, sixth, and seventh-grade students and their science teachers (two females, one male). Argument-based inquiry approach was used to design and implement classroom discourse. Systematic observation approach was used to capture and classify the discursive types and purposes of the staged MDMs. For the MDMs displayed, six higher-order categories and accompanied 14 sub-categories (codes) were detected. The teachers staged MDMs for student-led monitoring, continuously reminding the emergent conceptual flows to the students, forcing the students to be internally consistent in idea sharing, controlling, and organising conceptual/procedural discourse, modelling strategic thinking and reformulating. The teachers also displayed the MDMs with the purposes of framing and cognitive engaging, adjusting cognitive load, managing discursive tension and scaffolding internalisation. Recommendations were offered for science teacher education.